1985
DOI: 10.1080/09553008514550761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melanin on Radiation Response of CHO Cells

Abstract: The effect of the presence of melanin on the response of mammalian cells to ionizing radiation was investigated in a model system utilizing the ability of Chinese hamster ovary cells to incorporate melanin by endocytosis. Cells were incubated in monolayer cultures from 2 to 20 hours with melanin prepared from 'beef eye' or synthesized by air oxidation of 3,4-dihydroxyphenylalanine. For asynchronous cultures, the survival curve parameters for cells incubated with both types of melanin were indistinguishable fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
5
10
0
Order By: Relevance
“…Electron microscopy study showed that cells from dark appearing spheroids contained high concentrations of melanosomes (Szekely et al, 1985). Two studies showed that the addition of exogenous melanin in CHO cells or the variation of melanin content in B16 melanoma cells did not influence radiation sensitivity (Hopwood et al, 1985;Stephens et al, 1986). Our results on R25 confirm this finding and further indicate that melanin content over the range found in the white, brown and black spheroids also did not influence thermal sensitivity.…”
supporting
confidence: 81%
“…Electron microscopy study showed that cells from dark appearing spheroids contained high concentrations of melanosomes (Szekely et al, 1985). Two studies showed that the addition of exogenous melanin in CHO cells or the variation of melanin content in B16 melanoma cells did not influence radiation sensitivity (Hopwood et al, 1985;Stephens et al, 1986). Our results on R25 confirm this finding and further indicate that melanin content over the range found in the white, brown and black spheroids also did not influence thermal sensitivity.…”
supporting
confidence: 81%
“…41 Studies on Chinese hamster-human hybrid ovary cells transfected with the tyrosinase gene demonstrated that melanin production protected against gamma radiation, 42 but in Chinese hamster ovary cells (melanin is incorporated by endocytosis) there was lack of protection against X-rays. 24 Likewise, Grossi et al 43 did not find melanin protection when studying the survival of human mammary epithelial cells incubated with melanin followed by exposure to X-rays and alpha particles. It is therefore possible that the protective activity of melanin requires selective association with melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Melanotic and amelanotic melanomas differ in their sensitivity to ionizing and UVR, [22][23][24][25] suggesting that inhibition of melanogenesis could play a role in melanoma therapy. 19 Experimentally, the significance of melanin presence for radioresistance of melanoma was described in Bomirski melanomas transplanted in hamsters, e.g., pigmented melanomas exhibited higher resistance to ionizing radiation compared to nonpigmented tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other investigations, melanin was shown to be ineffective at protecting against radiation damage. The effect of melanin on the response of mammalian cells to gamma-radiation was investigated in Chinese hamster ovary cells [15] and in mouse melanoma cells [16,17]. In these experiments, the variation of melanin content inside the irradiated cells did not influence their radiation sensitivity.…”
Section: Introductionmentioning
confidence: 99%